Impact of branding strategies on service delivery within Mogadishu's commercial banks, Somalia (International Journal of Management and Sustainability, 2025)
The study sought to establish the impact of branding strategies on service delivery within Mogadishu's commercial banks in Somalia. The study's target population was 15 commercial banks in Mogadishu. The unit of analysis was three marketing officers from the marketing department in each bank, giving a total of 45 respondents, and census was adopted. Information was gathered with the aid of a structured questionnaire whose validity and reliability had been determined beforehand. Data analysis was done through descriptive analysis, multiple linear regression, and correlation analyses. Brand association (p